2019
DOI: 10.4038/agrieast.v13i2.73
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foliar application of moringa (<i>Moringa oleifera</i>) leaf extract with recommended fertilizer on growth and yield of okra (<i>Abelmoschus esculentus</i>)

Abstract: to study the effects of different concentrations and frequencies of Moringa (Moringa oleifera) Leaf Extract (MLE) as a foliar application on growth and yield of okra (Abelmoschus esculentus) plants. This experiment was laid out in a Randomized Complete Block Design (RCBD) with three replicates with the following treatments; T0control (Distilled water), T1-10% MLE at once a week interval, T2-10% MLE at once in two weeks interval, T3-20% MLE at once a week interval, T4-20% MLE at once in two weeks interval, T5-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
4
9
0
1
Order By: Relevance
“…The highest values for plant height (65.07 cm) and RCD of (1.63 cm) (Table 1) were recorded in treatment of 50 ml EM (application of 50 ml moringa leaf extract on emergence stage). The lowest values for plant height (52.69 cm and 54.39 cm) and with RCD of (0.35 cm and 0.47 cm) (Figure 2) in the treatment of application of 25 ml and 50 ml moringa leaf extract 30 days before transplanting to the field and control, respectively and same result was also reported by Kanchani and Harris (2019). Application of moringa leaf extract with high concentration in the early stage of Cordia africana tree enhances the growth as well as diameter, but there is no effect when the extract was applied in the latter stage of the tree in the nursery.…”
Section: Effect Of Moringa Leaf Extract On the Growth Of Trees In Nurserysupporting
confidence: 82%
See 1 more Smart Citation
“…The highest values for plant height (65.07 cm) and RCD of (1.63 cm) (Table 1) were recorded in treatment of 50 ml EM (application of 50 ml moringa leaf extract on emergence stage). The lowest values for plant height (52.69 cm and 54.39 cm) and with RCD of (0.35 cm and 0.47 cm) (Figure 2) in the treatment of application of 25 ml and 50 ml moringa leaf extract 30 days before transplanting to the field and control, respectively and same result was also reported by Kanchani and Harris (2019). Application of moringa leaf extract with high concentration in the early stage of Cordia africana tree enhances the growth as well as diameter, but there is no effect when the extract was applied in the latter stage of the tree in the nursery.…”
Section: Effect Of Moringa Leaf Extract On the Growth Of Trees In Nurserysupporting
confidence: 82%
“…Similar researches was reported by Biswas et al (2016) on maize, Culver et al (2012) on tomatoes and Mvumi et al (2012) on beans and maize. This might be due to zeatin, which is the most common cytokinin in the extract, responsible for the improved plant height at an early growth (Kanchani & Harris, 2019…”
Section: Effect Of Moringa Leaf Extract On the Growth Of Trees In The Field Conditionmentioning
confidence: 99%
“…Minimum numbers of leaves plant -1 (91.67) were produced by control (0%) treatment. It is obvious from the results that snapdragon These findings also agree with[24] who reported that MLE at the rate of 10 % concentration increased the number of leaves plant -1 in okra. Similar findings were reported by[25] in sweet corn and[26] in garlic.…”
supporting
confidence: 90%
“…The moringa leaf extract (MLE) has been classified as one of the prominent bio-stimulants due to its rich minerals, free amino acids, vitamins, phytohormones, and antioxidant contents [12]. Moreover, the preparation of MLE in 80% ethanol or in water is both cost-efficient and eco-friendly [12]; therefore, it has been used as a natural growth promoter and/or stress-reducing agent for many plant species [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%